A follow-up study investigating changes in oral health-related quality of life (OHRQoL) in patients undergoing orthodontic treatment for Class II division 1 malocclusion: A longitudinal study - KHRAISHI, HADIL (Trinity College Dublin. School of Dental Sciences. Discipline of Dental Science, 2019)
The aim of the study is to evaluate the impact of orthodontic treatment on OHRQoL in children with Class II division 1 malocclusion. Secondary objectives included assessment of the level of agreement in rating the children's OHRQoL between parents and children, examination of the relationship between the perceived and normative aesthetic treatment needs and how the former relates to OHRQoL. Materials and Methods A consecutive sample of 74 patients aged 11-14 years with a 5a Index of Orthodontic Treatment Need (IOTN) was recruited. The children and their parents were asked to fill short forms of the Child Perception Questionnaire (CPQ11-14) and the Parental-Caregiver Perception Questionnaire (P-CPQ), respectively at four time points of the children's orthodontic treatment: T1 (prior to starting treatment), T2 (at the end of the functional appliance phase), T3 (following six months with upper and lower fixed appliances) and T4 (at the end of treatment, three months post-debond). Prior to starting the fixed appliance phase, the children were asked to score their corresponding Aesthetic Component (AC) of IOTN. A calibrated clinician also rated the AC of the children to represent the normative aesthetic treatment need. Results A total of 46 pairs of children and parents completed the questionnaires at the four time points. At the end of treatment, repeated measures analysis of variance (ANOVA) model has shown a statistically significant improvement (P<0.05) in the overall CPQ11-14 scores particularly in the emotional and social well-being sub-domains compared to pre-treatment scores. Across the four time points of measurement, the intraclass correlation coefficient (ICC>0.5) indicates a moderate level of agreement between parents and children in rating the children's OHRQoL. Poorer levels of agreement are observed at the emotional and social well-being dimensions (ICC<0.5) with the parents scoring higher mean values. The ICC between the self-reported AC of IOTN and those rated by the clinician reveals a moderate to a high level of agreement (ICC 0.529-0.767). The spearman correlation test found a weak correlation (ρ=0.062) between the self-reported AC of IOTN ratings and CPQ11-14 scores that was of no statistical significance (p=0.69). Conclusion: Orthodontic treatment of Class II division 1 in children is associated with improvement in OHRQoL particularly in the emotional and social well-beings dimensions. Parents tend to overestimate the emotional and social impact malocclusion and orthodontic treatment have on their children's OHRQoL. The children are found to be as conscious of their aesthetic treatment need, as clinicians would be. The subjective aesthetic treatment need does not relate to OHRQoL (as measured by CPQ11-14) suggesting several other factors other than dental aesthetics might play a role in influencing the subjective treatment need.
APPROVED
Keywords: Orthodontics; class ii division 1 malocclusion; oral health related quality of life; CPQ; OHRQOL